Economic Exploitation and Wali Adhal in Islamic Marriage: A Socio-Legal Study from Indramayu, Indonesia - Reza Fajri Hidayat; Achmad Kholiq (Journal of Indonesian Islamic Studies, 2026)
This study examines the phenomenon of wali adhal in Islamic marriage through a socio-legal analysis of a case in Pilangsari Village, Indramayu, Indonesia. While previous studies have primarily focused on the legal aspects of guardianship refusal and judicial mechanisms for transferring guardianship authority, limited attention has been given to economic exploitation as a motive underlying marriage obstruction. This research aims to analyze how economic interests shape guardianship practices and influence women’s access to marriage and legal protection. Employing a qualitative empirical legal research design with a socio-legal approach, data were collected through in-depth interviews, participant observation, and document analysis involving the prospective bride, prospective groom, lineage guardian, family members, community leaders, and officials from the local Office of Religious Affairs (KUA). The findings reveal that the guardian’s refusal to approve the marriage constituted wali adhal because it was not based on legitimate Islamic legal considerations but rather on economic motives, including financial demands and efforts to maintain long-standing economic benefits derived from the daughter’s income as an Indonesian migrant worker. The study further demonstrates that economic exploitation was reinforced by patriarchal authority and unequal family power relations, transforming guardianship from a protective institution into a mechanism of economic control. As a consequence, the prospective bride ultimately entered into an unregistered (sirri) marriage after mediation efforts failed. This study contributes to Islamic family law scholarship by introducing economic exploitation as an analytical framework for understanding contemporary manifestations of wali adhal and highlights the importance of strengthening legal literacy, improving access to justice, and enhancing institutional protection for women facing guardianship-related marriage obstruction.